Purinergic System - Dulce Bagatini, Margarete (Biochemistry, 2022)
Characterized as a common signaling pathway between cells, the purinergic system is capable of modulating physiological and biochemical processes. Composed of signaling molecules, regulatory enzymes, and specific receptors, this organization can modulate several basal pathways of the organism. It is understood that purinergic signaling is present in all aspects of immunity and inflammation and studies show that extracellular ATP and its adenosine metabolite are the main mediators of response. These occur since most immune cells express P2 and P1 receptors, which are sensitive to the ATP and adenosine molecules, respectively. This book describes the purinergic system and its correlation with the health and disease process.